Leachate analysis of green and fired-clay bricks incorporated with biosolids. (August 2017) - Ukwatta, Aruna; Mohajerani, Abbas
Highlights: Engineering properties, TG & DTG curves of ETP and WTP biosolids are discussed. Leachates of heavy metals from green and fired biosolids-bricks are analysed. 43–99% of 13 heavy metals leaching from green bricks was immobilized during firing. Adding biosolids in fired-bricks is a viable method for inerting the heavy metals. Physico-mechanical properties of bricks incorporated with biosolids are discussed. Abstract: The substantial increase in biosolids production throughout the world requires sustainable routes for reuse. This study describes the leaching behaviour of potentially hazardous metals from the green and fired bricks incorporating four different biosolids samples from the Eastern treatment plant (ETP) and Western treatment plant (WTP) in Melbourne. The biosolids samples were characterized by XRD, XRF, TGA, particle size distribution, and organic content. The leaching of As, Ag, Ba, Be, Cd, Cr, Cu, Mo, Ni, Pb, Sb, Se, and Zn was evaluated for both the green and the fired bricks according to the Toxicity characteristic leaching procedure (TCLP) and the Australian bottle leaching procedure (ABLP). The leaching of heavy metals from both the green and the fired bricks was compared to investigate the effect of firing on the leaching capability of bricks. The results showed that the leaching of heavy metals from fired bricks was significantly lower than that for the green bricks. The ABLP concentrations of heavy metals were higher than those found using the TCLP method, mainly due to the higher specific surface area of the particles used in the ABLP method. Moreover, bricks were evaluated by the technological properties, such as compressive strength, density and water absorption.